Characterization and Performance Test of Palm Oil Based Bio-Fuel Produced Via Ni/Zeolite-Catalyzed Cracking Process - Sri Kadarwati; Sri Wahyuni (International Journal of Renewable Energy Development, 2015)
Catalytic cracking process of palm oil into bio-fuel using Ni/zeolite catalysts (2-10% wt. Ni) at various reaction temperatures (400-500oC) in a flow-fixed bed reactor system has been carried out. Palm oil was pre-treated to produce methyl ester of palm oil as feedstock in the catalytic cracking reactions. The Ni/zeolite catalysts were prepared by wetness impregnation method using Ni(NO3)2.6H2O as the precursor. The products were collected and analysed using GC, GC-MS, and calorimeter. The effects of process temperatures and Ni content in Ni/zeolite have been studied. The results showed that Ni-2/zeolite could give a yield of 99.0% at 500oC but only produced gasoline fraction of 18.35%. The physical properties of bio-fuel produced in this condition in terms of density, viscosity, flash point, and specific gravity were less than but similar to commercial fuel. The results of performance test in a 4-strike engine showed that the mixture of commercial gasoline (petrol) and bio-fuel with a ratio of 9:1 gave similar performance to fossil-based gasoline with much lower CO and O2 emissions and more efficient combustion